Career engagement among university students: The role of parent-child career goal congruence and support - Fauzia, Fika Afifah; Widyowati, Arini (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
During the transition to adulthood, students are increasingly require are required to demonstrate active engagement in planning and managing their career development. This engagement is shaped by contextual factors, including the degree of alignment between students’ and parents’ career goals and the support received from parents. However, empirical research on career engagement among Indonesian university students,particularly studies examining its connection with parental factors, remains limit. This study aims to investigate the association between parent-child career goal congruence, parental support, and career engagement. A total of 224 active students participated in this study. Data were collected using three instruments: the Career Engagement Scale (α=0.84), the Parent-Child Career Goal Congruence Scale (α=0.89), and the Parental Support Scale (α=0.87). Multiple linear regression analysis revealed a significant association between parent-child career goal congruence, support, and career engagement. These findings highlight the potential for parents and career counselors to enhance students' career engagement by fostering alignment between parental and student career goals, and by providing consistent parental support.